2019
DOI: 10.3390/urbansci3030071
|View full text |Cite
|
Sign up to set email alerts
|

A Statistically Rigorous Approach to Experimental Design of Vertical Living Walls for Green Buildings

Abstract: Living walls (LW) have been widely proposed as a form of green infrastructure to improve aesthetics, energy consumption, and microclimate in urban environments by adding densely-planted vegetation to the outside walls of buildings. Scientific studies using multiple treatments in a single LW face challenges due to the close physical proximity of different treatments, particularly the potential for plants above to influence those below. A study on a west-facing LW was undertaken to investigate 36 unique treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The design and location of a LW from [27] was replicated and adapted in this study. The LW comprised 144 Elmich Versiwall modular LW pots.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and location of a LW from [27] was replicated and adapted in this study. The LW comprised 144 Elmich Versiwall modular LW pots.…”
Section: Methodsmentioning
confidence: 99%
“…Plant selection may involve consideration of foliage, colour, texture, leaf shape, plant size, vigour and growth habit [20,21]. Previous research on LWs have utilised perennial [22][23][24], drought-tolerant succulent [25], salttolerant [26] and native plants [8,27]. One previous study recommended evergreen shrubs to be planted on living walls, while evergreen climbing species were preferred for green façades [28].…”
Section: Introductionmentioning
confidence: 99%
“…The individual pots were 195 mm wide, 207 mm high and 192 mm deep, yielding a total volume of 1.8 L that contained 1.5 L of soil substrate. The living wall was fitted with a drip irrigation system comprising pressure-compensating drippers [20].…”
Section: Methodsmentioning
confidence: 99%
“…Six plant species were selected, namely, Goodenia varia (GV), Einadia nutans (EN), Dichondra repens (TT) Dianella revoluta (DR), Myoporum parvifolium (MP) and Westringia fruticosa (WF). There were 36 unique combinations of irrigation-substrate-plant, and each was replicated four times in the LW following a statistical design that included carry-over effects [20]. The full experimental design of the LW's plant-substrate-irrigation system is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies [21,[29][30][31] have shown that VGS protect against direct, diffuse, and reflective solar radiation. The ability of VGS to absorb noise and increase the acoustic insulation of buildings is well-documented [32].…”
Section: Introductionmentioning
confidence: 99%